The Effectiveness of Gratitude Training on Reducing Parenting Stress in Parents Who Have Children with Special Needs - Yuniar, Hesti Firza; Suroso, Suroso; Farid, Muhammad (International Journal of Research in Counseling, 2023)
As the number of children with special needs in Indonesia increases, the number of cases of maltreatment of children with special needs by parents also increases. Caring for children with disabilities who have inhibitions and limitations and require special treatment brings its own difficulties for parents and can cause great stress. This study aims to determine whether gratitude training is effective in reducing parenting stress in parents of children with special needs. The research subjects were 20 parents who have children with special needs in the Sidoarjo and Surabaya areas. The type of research used is experimental method research, with experimental design One Group Pretest Postest Design. The parenting stress scale in this study, measured using the Indonesian version of the Parental Stress Scale (PSS) which has proven its validity and reliability and has been tested on 449 parents in Indonesia. The results of the hypothesis test study in this study, using Wilcoxon statistical test = -3.834 and significance = 0.000 (p < 0.05), and the average level of parenting stress during the pretest (mean = 46.20) was higher than the average parenting stress during the postest (mean = 28.25) meaning that gratitude training was effective in reducing parenting stress in parents who have Children with Special Needs, It was proven that the average level of parenting stress during the postest decreased compared to the average parenting stress during the pretest.